Modulation of ATM enhances DNA repair in G2/M phase of cell cycle and averts senescence in Fuchs endothelial corneal dystrophy - Shazia Ashraf; Neha Deshpande; Queenie Cheung; Jeffrey Boakye Asabere; Raymond Jeff Wong; Alex G. Gauthier; Mohit Parekh; Yadav Adhikari; Geetha Melangath; Ula V. Jurkunas (Communications Biology)
Abstract Fuchs Endothelial Corneal Dystrophy (FECD) is an aging disorder characterized by expedited loss of corneal endothelial cells (CEnCs) and heightened DNA damage compared to normal CEnCs. We previously established that ultraviolet-A (UVA) light causes DNA damage and leads to FECD phenotype in a non-genetic mouse model. Here, we demonstrate that acute treatment with chemical stressor, menadione, or physiological stressors, UVA, and catechol estrogen (4-OHE2), results in an early and increased activation of ATM-mediated DNA damage response in FECD compared to normal CEnCs. Acute stress with UVA and 4OHE2 causes (i) greater cell-cycle arrest and DNA repair in G2/M phase, and (ii) greater cytoprotective senescence in NQO1 −/− compared to NQO1 +/+ cells, which was reversed upon ATM inhibition. Chronic stress with UVA and 4OHE2 results in ATM-driven cell-cycle arrest in G0/G1 phase, reduced DNA repair, and cytotoxic senescence, due to sustained damage. Likewise, UVA-induced cell-cycle reentry, gamma-H2AX foci, and senescence-associated heterochromatin were reduced in Atm-null mice. Remarkably, inhibiting ATM activation with KU-55933 restored DNA repair in G2/M phase and attenuated senescence in chronic cellular model of FECD lacking NQO1. This study provides insights into understanding the pivotal role of ATM in regulating cell-cycle, DNA repair, and senescence, in oxidative-stress disorders like FECD.